2015
DOI: 10.1016/j.athoracsur.2015.05.105
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Histology of Aortic Dilatation Associated With Bileaflet Versus Trileaflet Aortic Valves

Abstract: More severe histologic abnormalities associated with trileaflet aortic valve compared with BAV, especially when stratified by diameter, do not support a more aggressive approach to surgical intervention for dilatation associated with BAV. Indeed, if based on histologic diagnosis alone, our findings are suggestive that the converse might be true. Additionally, the lack of correlation between aortic diameter and histologic abnormality in the setting of BAV highlights the inadequacy of diameter alone as a criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
4
18
0
1
Order By: Relevance
“…6 It has been shown that a nondilated BAV ascending aorta has degraded elastic lamella fibers compared with nondilated TAV ascending aorta. 7 However, a study by Heng and colleagues 8 has suggested a more severe histologic abnormality in dilated TAV versus BAV aortas. Further extending these concepts, it has been suggested that the cause of aortic dilation is different in patients with aortic stenosis (AS) and aortic insufficiency (AI) and is based on TAV and BAV morphology, histology, and hemodynamic flow patterns.…”
Section: See Editorial Commentary Page 433mentioning
confidence: 99%
“…6 It has been shown that a nondilated BAV ascending aorta has degraded elastic lamella fibers compared with nondilated TAV ascending aorta. 7 However, a study by Heng and colleagues 8 has suggested a more severe histologic abnormality in dilated TAV versus BAV aortas. Further extending these concepts, it has been suggested that the cause of aortic dilation is different in patients with aortic stenosis (AS) and aortic insufficiency (AI) and is based on TAV and BAV morphology, histology, and hemodynamic flow patterns.…”
Section: See Editorial Commentary Page 433mentioning
confidence: 99%
“…The complexity is further confounded by the findings of Heng and colleagues. In this recent study, tissue pathology was compared between TAV and BAV patients at matched aortic diameters(76). At odds with conventional wisdom, more severe histologic abnormalities were found in trileaflet aortic valve aorta as compared with BAV, especially when stratified by diameter.…”
Section: Cellular and Molecular Mechanisms Of Bav Aortopathymentioning
confidence: 99%
“…On the other hand, a strong genetic predisposition has been suggested to contribute to aortopathy in BAV patients. Interestingly, a recent study showed that TAV aortopathy was associated with more severe histologic abnormalities compared to BAV aortopathy, especially when stratified by diameter (Heng et al, 2015). Properly assessing the diagnostic value of novel imaging biomarkers requires further work in this area to gain a better appreciation of the differences in the development of BAV vs. TAV aortopathy.…”
Section: Imaging Hemodynamic Biomarkers and Aortic Wall Pathologymentioning
confidence: 99%